2023
DOI: 10.3390/cancers15072024
|View full text |Cite
|
Sign up to set email alerts
|

The Glioma Immune Landscape: A Double-Edged Sword for Treatment Regimens

Abstract: Immune cells constitute a major part of the tumor microenvironment, thereby playing an important role in regulating tumor development. They interact with tumor cells, resulting in the suppression or promotion of glioma development. Therefore, in recent years, scientists have focused on immunotherapy that involves enhancing the immune response to fight the battle against cancer more effectively. While it has shown success against different cancer types, immunotherapy faces major roadblocks in glioma treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 226 publications
0
12
0
Order By: Relevance
“…Gliomas exhibit a distinct tumor microenvironment, largely due to the presence of the blood–brain barrier [ 26 ]. During glioma progression, the infiltrating macrophages, Tregs and MDSCs have been shown to have protumor and immunosuppressive effects [ 26 , 27 ]. To examine the potential role of these immune cells in the prognosis value of the PEX5-dependent model, we computed the abundance of the three types of immune cells in each glioma patient through ssGSEA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gliomas exhibit a distinct tumor microenvironment, largely due to the presence of the blood–brain barrier [ 26 ]. During glioma progression, the infiltrating macrophages, Tregs and MDSCs have been shown to have protumor and immunosuppressive effects [ 26 , 27 ]. To examine the potential role of these immune cells in the prognosis value of the PEX5-dependent model, we computed the abundance of the three types of immune cells in each glioma patient through ssGSEA [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gliomas present a complex and unique immune microenvironment, largely due to the presence of the blood–brain barrier [ 26 ]. Within this microenvironment, various immune cell populations coexist, including macrophages, resident microglia, MDSCs, T cells, natural killer (NK) cells, and a small number of B cells [ 27 ]. Studies have shown that macrophages, Tregs, and MDSCs exert protumor and immunosuppressive effects during the progression of gliomas [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Killer cell immunoglobulin-like receptors (KIRs) on NK cells play a critical role in NK cell function by interacting with MHC class I molecules on target cells. In glioma, increased KIR expression on NK cells and decreased ligand expression on tumor cells reduce NK cell activity [ 152 ]. However, studies indicate that activating KIR genes enhances NK cell efficacy against pediatric tumors [ 153 ].…”
Section: Main Textmentioning
confidence: 99%